The electoral law and its impact on party competition in Central America - Cascante, María José (2014)
This article explains the influence of the electoral law on decentralization of competition in Central America. To achieve this objective, first there is a description of multilevel competition Guatemala, Honduras, El Salvador, Nicaragua and Costa Rica, through the party system indicators and local actors. Then it is explored the influence of the electoral law from the perspective of local competition.